Chorthippus bornhalmi new to Lebanon and Jordan, and Eremippus persicus new to Jordan (Orthoptera: Acrididae) - Massa, Bruno (Fragmenta entomologica, 2021)
The author reports for the first time the presence of Chorthippus (Glyptobothrus) bornhalmi Harz, 1971 in Jordan and Lebanon, and Eremippus persicus Uvarov, 1929 in Jordan.